Hardware development for the socialight prototype 2 - Kua, Hui Lin (2019)
The aim of this final project is to create a second prototype of an Arduino controlled interactive smart lamp called Socialight where users get to control the lamp via an Android application. The wireless communication between Arduino and Android is made via Bluetooth. Using an Arduino Nano board, control of each LED is made possible with the board as the main control unit of the lamp. This report aims to document the process of incorporating latest technology to the hardware development of second prototype of a smart lamp together with design of the lamp exterior. This report will provide a detailed documentation of the choices of hardware to match up to latest technologies, the methodology adopted in development of Arduino and lamp exterior design as well as the challenges faced throughout the project by the student. The report ends with a conclusion where limitations and recommendations for future work are identified.